The proactive maintenance for the irreversible sulfation in lead-based energy storage systems with a novel resonance method. (October 2021) - Tao, Shengyu; Fan, Hongtao; Lei, Yang; Xu, Xin; Sun, Yaojie; You, Bo; Gao, Yunfang
Highlights: Proactive maintenance of the lead-based energy storage system. Instinct electrical capacitive effect. Resonance method. Simultaneous, non-invasive sulfation diagnosis and restoration. Life cycle energy storage system management. Abstract: In this paper, the irreversible sulfation in lead acid battery (LAB) is essentially reconsidered as an electrical capacitive effect from an interdisciplinary perspective. A proactive maintenance concept based on the resonance method is first introduced to interpret the electrochemical processes of the irreversible sulfation for simultaneous diagnosis and restoration. The effectiveness of the restoration is verified by an average of 23% impedance decrease and an average of 8.6% capacity increase, which are consistent with the morphological change from a dense, tight connections to a coarsen, porous electrode surface. In terms of the diagnosis accuracy, the electrical capacitive effect is determined by measuring the break frequency of the LAB, where an 87.7% estimation accuracy is achieved compared to the analytical result from Nyquist curve. With the proposed integration method, it becomes possible to proactively maintain the LABs in lifecycle (separate service stages) non-invasively with both field convenience and electrochemical interpretation, which will act as a part of highly reliable, environment friendly and sustainable lead-based energy storage systems in the future. Graphical abstract: Image, graphical abstract